Optimization of Tensile Strength Behavior in 3D‐Printed PLA With 10% Terminalia chebula Nanocomposites: Influence of Strain Rate, Orientation, and Infill Percentage - R. Saravanan; Muthuselvan Balasubramanian; T. Sathish; Jayant Giri; A. Johnson Santhosh; Taoufik Saidani; Bashar Tarawneh (Engineering Reports)
ABSTRACT This study aims to investigate and maximize the tensile strength behavior of polylactic acid (PLA) 90% and Terminalia chebula nanoparticle (TCNP) 10% composites fabricated using fused deposition modeling (FDM) under varying strain rates (3, 6, 9 mm/min), orientations (0°, 45°, 90°), and infill percentages (30%, 60%, 90%). The tensile strength was analyzed to assess the combined influence of these parameters on the mechanical performance of the composites. At a low strain rate of 3 mm/min, the composites exhibited the highest tensile strength due to enhanced molecular alignment and stress redistribution, achieving maximum values in the 0° orientation across all infill percentages. Increasing the strain rate reduced tensile strength, with the material transitioning from ductile to brittle failure, especially at 9 mm/min, where rapid deformation hindered molecular realignment. The 0° orientation consistently demonstrated superior tensile strength due to efficient load transfer along printed layers, while the 90° orientation exhibited the weakest performance, attributed to stress concentrations at interlayer bonds. Higher infill percentages, 60% and 90%, improved material density, enhancing tensile strength but diminishing under higher strain rates. The study highlights the optimal mechanical performance of a maximum tensile strength of 45.67 ± 2.28 MPa, which was achieved at 90% infill, 3 mm/min strain rate, with 0° orientation, making it suitable for load‐bearing applications. The findings provide insights into the tailoring of 3D‐printed PLA‐TCNP composites for specific applications, balancing strength, ductility, and controlled failure mechanisms.